Simultaneous Registration of Image Sequences – a novel singular value based images similarity measure. Issue 1 (17th December 2018) - Brehmer, Kai; Wacker, Benjamin; Modersitzki, Jan
Abstract: The comparison of images is an important task in image processing. For a comparison of two images, a variety of measures has been suggested. However, applications such as dynamic imaging or serial sectioning provide a series of many images to be compared. When these images are to be registered, the standard approach is to sequentially align the j ‐th image with respect to its neighbours and sweep with respect to j . One of the disadvantages is that information is distributed only locally. We introduce an alternative so‐called SqN approach. SqN is based on the Schatten‐ q ‐norm of the image sequence gradients, i.e. rank information of image gradients of the whole image sequence. With this approach, information is transported globally. Our experiments show that SqN gives at least comparable registration results to standard distance measures but its computation is about six times faster.